Comparison of two phenotypically distinct lattice corneal dystrophies caused by mutations in the transforming growth factor beta induced (TGFBI) gene. Issue 3 (16th February 2014) - Poulsen, Ebbe Toftgaard; Runager, Kasper; Risør, Michael W.; Dyrlund, Thomas F.; Scavenius, Carsten; Karring, Henrik; Praetorius, Jeppe; Vorum, Henrik; Otzen, Daniel E.; Klintworth, Gordon K.; Enghild, Jan J.; Semba, Richard D.; et al.
<x xml:space="preserve">Abstract</x> Purpose In this study, we investigated whether the phenotypic difference observed between two lattice corneal dystrophy type 1 (LCD type 1) cases caused by either a single A546D substitution or an A546D/P551Q double substitution in TGFBIp (transforming growth factor beta induced protein) can be ascribed to (i) a difference in the proteomes of corneal amyloid deposits, (ii) altered proteolysis of TGFBIp, or (iii) structural changes of TGFBIp introduced by the P551Q amino acid substitution. Experimental design Amyloid deposits were isolated from the corneas of two siblings with LCD type 1 resulting from A546D/P551Q mutations in the TGFBI gene using laser capture microdissection and subsequently analyzed by LC‐MS/MS. Proteolytic processing of TGFBIp was addressed by counting peptide spectra. Lastly, to study the possible effect of the P551Q substitution, recombinant FAS1–4 domain variants were subjected to in vitro stability assays. Results The amyloid proteomes and TGFBIp processing of the two A546D/P551Q LCD type 1 cases were similar to each other as well as to the A546D amyloid proteome previously reported by us. The stability assays revealed a minor destabilization of the FAS1–4 domain upon the addition of the P551Q mutation, moreover, it resulted in different accessibility to tryptic cleavage sites between the A546D and A546D/P551Q mutant FAS1–4 domain variants. Conclusion and clinical relevance The difference in A546D and A546D/P551Q LCD type 1 phenotypes cannot be ascribed to altered corneal amyloid composition or altered in vivo proteolytic processing of TGFBIp. Instead, a small difference in thermodynamic stability introduced by the P551Q mutation most likely causes structural changes of TGFBIp. The MS proteomics data have been deposited to the ProteomeXchange with identifier PXD000307 (http://proteomecentral.proteomexchange.org/dataset/PXD000307).